Adherence to secondary antibiotic prophylaxis for patients with rheumatic heart disease diagnosed through screening in Fiji. Issue 12 (28th October 2016) - Engelman, Daniel; Mataika, Reapi L.; Kado, Joseph H.; Ah Kee, Maureen; Donath, Susan; Parks, Tom; Steer, Andrew C.
Abstract: Objectives: Echocardiographic screening for rheumatic heart disease (RHD) can detect subclinical cases; however, adequate adherence to secondary antibiotic prophylaxis (SAP) is required to alter disease outcomes. We aimed to investigate the adherence to SAP among young people with RHD diagnosed through echocardiographic screening in Fiji and to investigate factors associated with adherence. Methods: Patients diagnosed with RHD through echocardiographic screening in Fiji from 2006 to 2014 were included. Dates of benzathine penicillin G injections were collected from 76 health clinics nationally from December 2011 to December 2014. Adherence was measured using the proportion of days covered (PDC). Multivariate logistic regression analysis was used to identify characteristics associated with any adherence (≥1 injection received) and adequate adherence (PDC ≥0.80). Results: Of 494 patients, 268 (54%) were female and the median age was 14 years. Overall, 203 (41%) had no injections recorded and just 33 (7%) had adequate adherence. Multivariate logistic regression showed increasing age (OR 0.93 per year, 95% CI 0.87–0.99) and time since diagnosis ≥1.5 years (OR 0.53, 95% CI 0.37–0.79) to be inversely associated with any adherence. Non‐iTaukei ethnicity (OR 2.58, 95%CI 1.04–6.33) and urban residence (OR 3.36, 95% CI 1.54–7.36) were associated with adequate adherence, whereas time since diagnosis ≥1.5 years (OR 0.38, 95%CI 0.17–0.83) was inversely associated with adequate adherence. Conclusions: Adherence to SAP after screening in Fiji is currently inadequate for individual patient protection or population disease control. Secondary prevention should be strengthened before further screening can be justified.